Adaptive wheel exercise for mouse models of Parkinson’s Disease - Skelton, Henry; Grogan, Dayton; Kotlure, Amrutha; Berglund, Ken; Gutekunst, Claire-Anne; Gross, Robert (Journal of neuroscience methods, 2025)
Physical exercise has been extensively studied for its therapeutic properties in neurological disease, particularly Parkinson’s Disease (PD). However, the established techniques for exercise in mice are not well suited to motor-deficient disease-model animals, rely on spontaneous activity or force exercise with aversive stimuli, and do not facilitate active measurement of neurophysiology with tethered assays. Motorized wheel exercise may overcome these limitations, but has not been shown to reliably induce running in mice. We developed an apparatus and technique for inducing exercise in mice without aversive stimuli, using a motorized wheel that dynamically responds to subject performance. A commercially available motorized wheel system did not satisfactorily provide for exercise, as mice tended to avoid running at higher speeds. Our adaptive wheel exercise platform allowed for effective exercise induction in the 6-hydroxydopamine mouse model of PD, including with precise behavioral measurements and synchronized single-unit electrophysiology. Our approach provides a superior physical platform and programming strategy compared to previously described techniques for motorized wheel exercise. Unlike voluntary exercise, this allows for controlled experimental induction of running, without the use of aversive stimuli that is typical of treadmill-based techniques. Adaptive wheel exercise should allow for physical exercise to be better studied as a dynamic, physiological intervention in parkinsonian mice, as well as other neurological disease models. •Adaptive wheel exercise is a novel approach for exercise in mice.•The motorized wheel design described here improves on existing platforms.•Adaptive programming actively responds to subject performance.•In combination, this effectively induces running in motor deficient 6-OHDA mice.•It also allows behavioral quantification and synchronized electrophysiology.